Differentiation of volatile organic compounds in chili powders of different spiciness levels via E-nose, HS-GC–IMS, and chemometrics - Zhao, Shibo; Zhang, Meng; Ran, Yecheng; Yang, Zhou; Dong, Ruonan; He, Linlin; Jin, Wengang; Abd El-Aty, A. M. (Frontiers in Nutrition, 2025)
IntroductionChili powder is a widely used seasoning whose pungency largely depends on its capsaicin content and volatile compounds.MethodsThis study evaluated the capsaicin levels and pungency of three commercial chili powders labeled light, medium, and strong using a pungency meter. Volatile organic compounds (VOCs) were analyzed via electronic nose and headspace gas chromatography–ion mobility spectrometry (HS-GC–IMS) coupled with multivariate statistical analyses.ResultsCapsaicin concentrations in the medium and strong chili powders were significantly greater than those in the light group (p < 0.01). The Scoville heat unit (SHU) values were 604 (light), 1,585 (medium), and 1733 (strong). The electronic nose successfully differentiated samples on the basis of spiciness level. HS-GC–IMS identified 48 VOCs, mainly aldehydes (51.74–55.55%) and ketones (29.93–32.09%). Variable importance projection (VIP > 1, p < 0.05) highlighted 21 marker volatiles, whereas fold change analysis (FC > 2 or < 0.5) identified 14 differential compounds across sample groups. Key odorants such as (E, E)-2,4-heptadienal, butanal, 3-methylbutanal, and 2,3-butanedione were associated with flavor differences among the chili powders.ConclusionChili powders with varying spiciness levels exhibit notable differences in capsaicin content, VOC profiles, and distinctive flavor markers, which can be effectively characterized through integrated sensory and chemical analyses.